PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PADA PT. BURGER KING DI KOTA MATARAM - Erviva Fariantin; Ulfiyani Asdiansyuri; Hengki Samudra (Jurnal Inovasi Penelitian, 2021)
The development of the food industry is rapidly increasing marked by the increasing number of ready-to-eat foods in all of the world, including Indonesia. Ready-to-eat food has an impact on the emergence of people's needs for fast and instant food. The presence of fast food is immediately favored by the community because of its fast presentation, making it easy to eat anywhere, even while standing or walking. One fast food is Burger King. Burger King Corporation is a series of international fast food restaurants that sell burgers, fries and soft drinks. Burger King is one type of fast food restaurant that serves hamburgers as its main menu. Burger King already has several branches in Indonesia such as in Jakarta, Bandung, Surabaya, Bali and Lombok. The type of research used is associative research. The technique of collecting data uses questionnaires, literature studies and interviews. The population in this study were all consumers who bought products at Burger King. The sampling technique is purposive sampling using the formula from Roscoe obtained a sample of 50 respondents. While for processing data analyzed to test the validity and reliability using SPSS. The data analysis tool used is multiple linear regression, the results of this study indicate that product variables, prices, and promotions have a positive and significant effect on purchasing decisions at Burger King City of Mataram.